ANALISIS KECEMASAN MAHASISWA DALAM MENYELESAIKAN SKRIPSI - Husni Wakhyudin; Anggun Dwi Setya Putri (PGSD Universitas Muria Kudus, 2020)
The purpose of this study is to analyze the anxiety of communicating students with the supervisor in the thesis guidance process. This research method uses qualitative methodology. Data collection techniques used were questionnaire, interview, observation and documentation. The results showed that the anxiety of communicating students in the experience of communication interaction with the supervisor in the thesis guidance process occurred in students when compiling or doing thesis guidance. This results in students experiencing various kinds of anxiety, ranging from headaches, difficulty falling asleep, feeling tired, restlessness, nervousness, despair, depression, dizziness, thoughts become chaotic so that it impacts on others so that they become targets of anger. Factors that have the potential to be the cause of student anxiety in communication interactions with supervisors in the guidance process are internal and external factors.